Influence of structure geometry on ice pressure on a vertical foundation - Sand, Björnar; Fransson, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2009)
The interaction of ice sheets with rigid vertical structures is an important problem in the design of arctic offshore structures. These structures often experience an enormous ice load since the ice sheet fails by crushing. The finite element method is adopted to calculate ice forces on vertical structures of various shapes. The effect of material nonlinearities and friction between the ice and structure is taken into account. The ice is treated as a transversely isotropic, nonlinear material and formation of crushing or cracking is treated as a transformation of state. The contact interaction between the ice sheet and the structure is simulated with a contact formulation based on finite sliding interaction between a deformable body and a rigid body with Coulomb friction sliding. To verify the applicability of the proposed constitutive models, the numerical results obtained during the present study are compared with data from field measurements. Godkänd; 2009; Bibliografisk uppgift: USB; 20090814 (ysko)